2015
DOI: 10.2807/1560-7917.es2015.20.27.21183
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention in pertussis outbreak with high attack rate in cohort of adolescents with complete acellular pertussis vaccination in Valencia, Spain, April to May 2015

Abstract: Forty-three pertussis cases reported in May 2015 in Valencia were linked to a school outbreak where 90% of the students had been vaccinated. Cases were diagnosed upon paediatrician consultation and in hospital emergency units. Approximately half of the cases were students born in 2002, the first age cohort with complete shift to acellular pertussis vaccine. Public health intervention, visiting school premises to conduct interviews, sample collection and early antibiotic prophylaxis stopped further spread in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Many countries with long-standing vaccination programmes have reported a resurgence of pertussis, despite sustained high vaccine coverage [1-4]. …”
Section: Introductionmentioning
confidence: 99%
“…Many countries with long-standing vaccination programmes have reported a resurgence of pertussis, despite sustained high vaccine coverage [1-4]. …”
Section: Introductionmentioning
confidence: 99%
“…According to CDC's report in 2012, annual incidence of 107,473 was recorded in year 1922, Over 264000 cases were reported in 1934 ( fig. 2) and 183,866 cases in 1940, 32 . The CDC's 2012 report shows that pertussis disease is once again becoming a public health problem with 92% increase in incidence from the late 1990s to 2011 and beyond 32 ; 13 In recent Valencia outbreak in Spain, about 90% of the pertussis cases had been vaccinated with DTaP vaccine 39 .…”
Section: Reported Cases Of Pertussismentioning
confidence: 95%
“…In 2011, Torres and colleagues reported that 86.4% of the incidence cases in the adolescent group were well vaccinated (Torres et al, 2011). In the US, there is more than six DOI: 10.21522/TIJPH.2013.06.02.Art016 ISSN: 2520-3134 fold increase from 7867 in year 2000 to 48,277 in 2012, 32 and according to Eshofonie and colleagues, all the cases of 2012 outbreak in a Rural Texas were fully vaccinated with aP 13 . The alarming rate of reemergence of the disease especially among the vaccinated group raises concerns about the longevity and waning effect of the acellular vaccine, 42 ; 1 .…”
Section: Waning Of Immune Induced Effect Of Ap Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…20 Early contact tracing and chemoprophylaxis of contacts has been advanced as protective in control of school-based outbreaks. 21 Outbreak response immunization (ORI) has been employed if a particular group is disproportionately affected and it is feasible to reach and vaccinate this group in a relatively short period of time. 4 ORI is supplementary immunization given over and above the routine vaccination schedule, including to those who may be fully immunized or those who did not receive their scheduled vaccines.…”
Section: Recent Epidemiology Of Pertussismentioning
confidence: 99%